2021
DOI: 10.3390/jof7090731
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antifungal Combinations in Difficult to Treat Candida Infections

Abstract: Candida infections are varied and, depending on the immune status of the patient, a life-threatening form may develop. C. albicans is the most prevalent species isolated, however, a significant shift towards other Candida species has been noted. Monotherapy is frequently indicated, but the patient’s evolution is not always favorable. Drug combinations are a suitable option in specific situations. The aim of this review is to address this problem and to discuss the role of drug combinations in difficult to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 103 publications
0
20
0
Order By: Relevance
“…The drug is effective against a wide range of Candida spp., is well tolerated, and has a synergistic effect with amphotericin B. Flucytosine is used in combination with amphotericin B in invasive candidiasis in neonates with Candida meningitis due to its superb penetration into the cerebrospinal fluid. The use of flucytosine monotherapy is limited due to easily emerging resistance [ 162 , 163 , 164 , 165 ]. Hematologic and hepatic toxicities are associated with flucytosine administration.…”
Section: Treatment Of Invasive Candidiasismentioning
confidence: 99%
“…The drug is effective against a wide range of Candida spp., is well tolerated, and has a synergistic effect with amphotericin B. Flucytosine is used in combination with amphotericin B in invasive candidiasis in neonates with Candida meningitis due to its superb penetration into the cerebrospinal fluid. The use of flucytosine monotherapy is limited due to easily emerging resistance [ 162 , 163 , 164 , 165 ]. Hematologic and hepatic toxicities are associated with flucytosine administration.…”
Section: Treatment Of Invasive Candidiasismentioning
confidence: 99%
“…Compared to single drug-based monotherapy, synergistic combination therapy enhances drug effectiveness and reduces the emergence of drug resistance. Several in vitro and in vivo studies reported effectiveness of combinatorial approaches in treating fungal infections ( Spitzer et al., 2017 ; Vitale 2021 ). The synergistic activity in combinatorial approaches is achieved by the use of drug combinations which have different cellular targets or through the enhancement of bioavailability.…”
Section: Alternate Strategies For Effective Antifungal Therapymentioning
confidence: 99%
“…Their activity consists in the inhibition of lanosterol-14-alpha-demethylase, an enzyme involved in the basic step of ergosterol biosynthesis [26]. C. glabrata and C. krusei show high levels of resistance to fluconazole and other antifungals [27]. However, clinically important antifungal agents such as fluconazole or amphotericin B, flucytosine, echinocandins [28], itraconazole [2] or ketoconazole have not been found to be as effective against C. albicans biofilm than against suspended cells, and the concentrations required to reduce cell metabolic activity in biofilm are 5 to 8 times higher than the corresponding minimum inhibitory concentrations (MICs) [29].…”
Section: Introductionmentioning
confidence: 99%